STUDI EKSPERIMENTASI PENGARUH FLYWHEEL DAN VARIASI PERBANDINGAN SPROKET TERHADAP DAYA LISTRIK YANG DIHASILKAN OLEH ROAD POWER GENERATOR LIGHT MODEL SPEED TRAP VERTICAL SLIDING - bambang setyono; Ayu Setyaning Sayekti Poesoko; Zainul Arifin (Institut Teknologi Adhi Tama Surabaya, 2022)
Road power generator (RPG) is a device for generating electricity from the energy generated from the road. The wasted kinetic energy from the wheels of passing vehicles is converted into electrical energy. The purpose of this study was to determine the effect of flywheel variations and sprocket ratios on the electrical power generated. The research used the experimental method, which was to directly test the designed RPG equipment. The independent variables of the study were flywheel mass = 718 gr, 749 gr, 1538 gr, sprocket ratio 1:1, 2:1, 3:1 with the variable control vehicle passing two-wheeled type, rider weight 70 kg, vehicle interval crossing RPG 3 minutes . The results of the research are: (1) the greater the mass of the flywheel, the greater the electrical power generated, (2) the higher the sprocket ratio tends to produce greater electric power, (3) the combination of faster generator shaft rotation and greater moment of inertia. will eventually produce greater electrical power.